Repositorio digital de la diversidad entomológica de la micro cuenca del rio yungañan en el sector la esperanza. - Reinoso Quishpe, Raúl Danilo (2019)
In Ecuador, it is evidenced that there is a hues group of entomological species which must be known by the inhabitants of the different regions of our country, So People must identify their characteristics, means of habitat and their origin. In a review carried out on existing web repositories, it has been identified that there is a limited amount of Web Applications that allow the world to know about the rich variety of insects that our country has. For this reason, the propose is to design a web system to present the results of a research process related to the entomology of the Micro Basin of the Yungañan River as a multidisciplinary research process, in which teachers and students of the Agronomy Career are associated. The methodology used for the development of the design is (PHP) Hypertext Preprocessor because it allows us to create a dynamic software which helps to generate program profiles without any cost and allows us to access to new tools which are easy to handle and interfaces that streamlines the work between the system with the programmer. The database engine was developed in MySQL with an approximate of 15 tables that integrate programming with user interfaces. As a result, a dynamic web application is obtained, and it could be considered as a scientific database, due to the great variety of information related to every insect species, its characteristics and scientific information. It is concluded that this type of applications should be considered in research processes, due to its relevant information and could be considered as a source of bibliographic scientific information.